Study on the Utilization of Medicinal Plants by the Community of Uelawu Village, Konawe District, Southeast Sulawesi - Tahoangako, Sarmadhan Saputra; Santosa, Djoko; Fakhrudin, Nanang (Majalah Farmaseutik, 2023)
Ethnomedicine is the science related to ethnicity and medicine. Ethnomedicine studies are basically carried out to understand health culture from the point of view of local community knowledge, especially the medical system that has become a community tradition for generations. Local genius of the use of medicinal plants to prevent and treat various diseases has been passed down from generation to generation by ethnic groups in Southeast Sulawesi. Ethnomedicine research on medicinal plants in Uelawu Village, Konawe Regency, Southeast Sulawesi Province aims to find out the types of plants that are efficacious as traditional medicines, how to prepare them, the doses used and how to use them in traditional medicine. The research method used was snowball sampling, through interviews with the people of Uelawu Village using a questionnaire covering the type of disease, herb, or single plant used (local name of the plant, part of the plant used, and method of preparation). Each local plant name used is determined and its Latin name is determined and a herbarium is made. The results showed that in Uelawu Village, Konawe District, Southeast Sulawesi Province, there were 25 species from 15 plant families that were used by the traditional community of Uelawu Village as ingredients for plant ingredients. The most used part of the plant is the leaves. Preparation of medicinal plant ingredients by boiling and then drinking is the method most often used by traditional communities living in Uelawu Village in utilizing medicinal plants as a medium for traditional medicine.